2021
DOI: 10.3390/cells10040731
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin 2 Dysregulates Autophagy in High-Fat-Exposed Immune-Tolerant Macrophages

Abstract: Obesity increases morbidity and resource utilization in sepsis patients. The immune response in sepsis transitions from an endotoxin-responsive hyper- to an endotoxin-tolerant hypo-inflammatory phase. The majority of sepsis mortality occurs during hypo-inflammation. We reported prolonged hypo-inflammation with increased sirtuin 2 (SIRT2) expression in obese-septic mice. The effect of direct exposure to high-fat/free fatty acid (FFA) and the role of SIRT2 in immune cells during the transition to hypo-inflammati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
(76 reference statements)
0
7
0
Order By: Relevance
“…OTUD7B serves as a deubiquitinase of P62/SQSTM1 and enhances the degradation of IRF-3 [51,52]. SIRT2 dysregulates autophagy in highfat-exposed immune-tolerant macrophages, and the knockdown of SIRT2 increases basal autophagy [53][54][55]. With the combined analysis of DEGs and reports mentioned above, our study indicated that PTPN22, PRKN, OTUD7B, and SIRT2 genes were strongly correlated to the negative regulation of excessive expression of RIG-I.…”
Section: Discussionmentioning
confidence: 55%
“…OTUD7B serves as a deubiquitinase of P62/SQSTM1 and enhances the degradation of IRF-3 [51,52]. SIRT2 dysregulates autophagy in highfat-exposed immune-tolerant macrophages, and the knockdown of SIRT2 increases basal autophagy [53][54][55]. With the combined analysis of DEGs and reports mentioned above, our study indicated that PTPN22, PRKN, OTUD7B, and SIRT2 genes were strongly correlated to the negative regulation of excessive expression of RIG-I.…”
Section: Discussionmentioning
confidence: 55%
“…The biological-context-driven regulation of LC3 and autophagy need further evaluation. Also, while we have implicated SIRT2 in dysregulated autophagy with high-fat exposure, the effect of ethanol-exposure and SIRT2-PFKP interaction on autophagy in ethanol-exposed macrophages needs further evaluation ( 77 ).…”
Section: Discussionmentioning
confidence: 99%
“…SIRT2 is an NAD+-dependent deacetylase and is the only sirtuin protein found in the cytoplasm, mitochondria, and nucleus [36]. It can regulate autophagy in high-fat-exposed immune cells ( 39 ). Another member of the spermatogenesis-related protein family, SPATA2, is associated with the autoimmune disorder of psoriasis ( 40 ).…”
Section: Discussionmentioning
confidence: 99%